The 2nd International Research Conference on Sustainable Energy, Engineering, Materials and Environment 2018
DOI: 10.3390/proceedings2231431
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Simulation of a Building Energy Hub

Abstract: The development of technologies such as efficient multi-generation system, lead to realizing the benefits of integrated energy infrastructure such as electricity, natural gas, and heating networks, and thus a rapid movement toward multi-energy systems (MES). In such systems, different energy carriers and systems interact together in a synergistic way. An Energy hub (EH) can be defined as the place where the production, conversion, storage and consumption of different energy carriers takes place, is a promising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…However, only electricity and natural gas are considered in these studies so the energy cost and emission of EH are high. The solar energy and storage systems have been examined in EH planning problems that the objective function is minimizing the cost of energy and emission during the operation period shown in Barmayoon et al (2016); Wanga et al (2017) annual fee, which shown at study (Bayod-Rújula et al, 2018). The EH structure considered wind turbine (WT) and energy storages together with a mathematical formulation is developed by Pazouki and Haghifam (2016).…”
Section: International Journal Of Sustainable Energy and Environmentamentioning
confidence: 99%
See 1 more Smart Citation
“…However, only electricity and natural gas are considered in these studies so the energy cost and emission of EH are high. The solar energy and storage systems have been examined in EH planning problems that the objective function is minimizing the cost of energy and emission during the operation period shown in Barmayoon et al (2016); Wanga et al (2017) annual fee, which shown at study (Bayod-Rújula et al, 2018). The EH structure considered wind turbine (WT) and energy storages together with a mathematical formulation is developed by Pazouki and Haghifam (2016).…”
Section: International Journal Of Sustainable Energy and Environmentamentioning
confidence: 99%
“…© 2019 Conscientia Beam. All Rights Reserved.in a typical day it is an instant and is about 0.055 $/kWh(Pazouki and Haghifam, 2016;Wanga et al, 2017;Bayod- Rújula et al, 2018).…”
mentioning
confidence: 99%
“…It is simulated with a load of 850 kW in base year and grows 5% annually. The rated power and module type of the PV and WT are discrete values and are assumed in table 1 [[32]- [36]]. Analogously, the parameters of the utility grid are also presented in table 1 with an CO 2 emission tax probably enforced by the government of 0.4cent/kg [ [38], [38]].…”
Section: The Parameters Of Test Micro-gridmentioning
confidence: 99%
“…Energy demand matrix L is equal to coupling matrix C times the installed generating capacity of P and the renewable energy R. C 1 P can be developed as In (7), due to the value of η boiler,ele P boiler,ele which is equal to 0, the equation can be represented as For each EH system component, the following parameters are included: capacity, efficiency, capital cost, fixed cost, variable cost, and lifetime as reported in Table 2. The electric-ity net emission factor considered is 0.28 kg/kWh and 0.204 kg/kWh for natural gas [22].…”
Section: The Eh Structure and Matrix Representationmentioning
confidence: 99%
“…where G STC is the irradiation under standard test conditions (STC), which is equal to 1000 W/m 2 . In a conventional PV plant of crystalline silicon, the conversion efficiency is in the range 15%-20% so 75% to 80% of the solar energy is not being used effectively [22]. Besides, the unused solar energy will heat up the panel, causing a decrease in the efficiency of the electricity generation.…”
Section: The Eh Structure and Matrix Representationmentioning
confidence: 99%